Validation of the Idiopathic Hypersomnia Severity Scale in the Czech Republic - Jitka Bušková; Eva Miletínová; Tereza Dvořáková; Radana Měrková; Jana Krpešová; Soňa Nevšímalová; Martin Milata; Karolína Galušková; Simona Dostálová; Karel Šonka (Prague Medical Report)
We have verified the eligibility of the Idiopathic Hypersomnia Severity Scale (IHSS) as a basic clinical tool for determining the subjective severity of illness in patients with idiopathic hypersomnia (IH) in the Czech Republic. Total of 37 patients with a diagnosis of IH (9 men, 28 women, mean age 40.2 ± 12.8) completed the IHSS scale. At the same time, they were instructed to complete the Epworth Sleepiness Scale (ESS), the Fatigue Severity Scale (FSS), the Hospital Anxiety and Depression Scales (HADS-A and HADS-D), and a short version of the Quality of Life Questionnaire (SF-36). The control group consisted of 88 ageand sex-matched healthy volunteers. The IHSS scale showed good internal consistency of the questionnaire using Cronbach’s α, which was 0.88. The KMO (Keiser-Meyer-Olkin index) was 0.72, confirming sufficient structural validity of the questionnaire. The correlation of the total IHSS score with the ESS (ρ = 0.59, p=0.0001) and FSS (ρ = 0.84, p<0.0001) as well as with the HADS-A scales (ρ = 0.64, p<0.0001), HADS-D (ρ = 0.79, p<0.0001) and SF-36 in both the mental (ρ = –0.85, p<0.0001) and physical health (ρ = –0.66, p<0.0001) components. The IHSS is a convenient and easy-to-apply clinical tool to assess subjective severity of illness, which describes well the symptoms of idiopathic hypersomnia and assesses their impact on health and daily activities.